Pengaruh FoMO (Fear of Missing Out) dalam Perspektif Gen Z terhadap Pesta Demokrasi 2024 - Agata Fanny Pakpahan; Dadi Mulyadi Nugraha; Hanifah El Faizah; Levina Lidya Maheswari; Muhtarom Nur Rasyid; Shabrina Zainuba Azahra; Yesa Rismawati (LPPM Politeknik Pratama, 2024)
Generation Z as a component of society born from 1996 to 2012 grew up with high exposure to social media content which certainly presents many benefits and complex challenges. One of the challenges is FoMO (Fear of Missing Out), always wanting to follow what is a public trend regardless of the impact on oneself and society. Using the literature study method, this research aims to assess the influence of FoMO on Generation Z's participation in the democratic party through the lens of identity theory. Social media seems to provide the capability to monitor all activities carried out by individuals and groups out there without being limited by distance and time. In political years, social media is often used to freely disseminate political content (political practitioners' campaigns) which causes Generation Z to get over information, thus influencing Generation Z's perspective in determining their choices. Generation Z tends to follow the characteristics of their peers, which can encourage generation Z to actively participate in political participation. There are several solutions to these problems. First, inclusive political education is needed for the community, especially generation Z, so as not to destroy unity in the midst of different political choices. We can also use FoMO itself to disseminate persuasive narratives so that generation Z is more encouraged to participate in healthy politics. Then with the holding of political discussions in various facilities, it is hoped that the organizers will be able to provide political understanding to generation Z and the entire community so that the level of FoMO in politics can decrease. Therefore, it is necessary to have a deep understanding of the FoMO phenomenon and the special strategies that generation Z must take in facing the 2024 democratic party.